Knowledge and practice of universal work precautions among Junior doctors - Goel, Pawan Kumar; Garg, K S; Singh, V J; Bhatnagar, M; Chopra, H; Bajpai, K S (Indian Journal of Community Health, 2003)
Research Problem : What is the knowledge and practice of Universal Work Precautions among Junior Doctors ? Objectives : (1) To assess the knowledge about universal work precautions and source of information. (2) To assess the practices of universal work precautions. (3) To assess the knowledge of hospital waste management in the concerned hospital. Study Design : Self administered oral questionnaire. Setting and Participants : 138 Junior Doctors from Sardar Vallabh Bhai Patel Hospital associated with L.L.R.M. College, Meerut. Study Variables : Universal work precautions. Statistical Analysis : By proportions. Result : In all 79.0% of Junior Doctors had knowledge about universal work precautions the major source of information being the books (69.0%). However the practice of these precautions was very low. Only 47.8% doctors were checking the integrity of thier skin with spirit/ alcohol, 45.7% were using water proof dressing if cut/abrasion was present, 68.2% were throwing the used gloves indiscriminately and 66.4% were leaving the spilled over blood/body fluids as such. Conclusion and Recommendations : Poor bookish knowledge and lack of sensitisation arc exposing junior doctors to the hazardous infections. So the need of the hour is to conduct aggressive teaching as well as training sessions to all of them including para- professionals also